Communication Mode Among Malaysians - Kuang, Ching Hei; Wong, N.L.; David, Maya Khemlani (2010)
Malaysia is a multicultural society which comprises three dominant ethnic groups: Malays (68%), Chinese (28%), Indians (10%) with other minorities (10%) (The Star July 21, 2009). Most Malaysians tend to behave in ways that could be predictably Asian, that is keeping a low profile when it comes to personality issues and tending to keep things to themselves rather than highlighting them. However, there is a slight difference in how the three ethnic groups communicate when it comes to the discussion of particular issues. This study looks at how Malaysians view ‘silence’ as a tool in human communication. Using surveys as our instrument to extract data, self-administered questionnaires were carried out on 661 respondents. SPSS was used to analyze data. Our findings reveal that Malaysians prefer words to silence when communicating with others. However, most prefer to keep silent when issues involving money are being discussed. We also found that a majority of Malaysians would not hesitate to ask directly when they discover their partners/spouses committing adultery. Of the three ethnic groups, our findings suggest that Malaysian Indians talk more than the others.